2009
DOI: 10.1113/jphysiol.2009.172510
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of visceral adipose tissue‐derived serine protease inhibitor by nutritional status, metformin, gender and pituitary factors in rat white adipose tissue

Abstract: Visceral adipose tissue-derived serine protease inhibitor (vaspin) is a recently discovered adipocytokine mainly secreted from visceral adipose tissue, which plays a main role in insulin sensitivity. In this study, we have investigated the regulation of vaspin gene expression in rat white adipose tissue (WAT) in different physiological (nutritional status, pregnancy, age and gender) and pathophysiological (gonadectomy, thyroid status and growth hormone deficiency) settings known to be associated with energy ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
60
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 40 publications
5
60
0
4
Order By: Relevance
“…In the insulin-resistant group, vaspin significantly declined during the oGTT, somehow inversely mirroring the course of insulin. This finding is coherent with the observation of a meal-related decline in vaspin levels 11,16 and may indicate that glucose and/or insulin may have acute suppressive effects of circulating vaspin levels and/or that food-related effects such as vagal activation are involved. Tan et al 10 identified glucose as a vaspin-releasing agent, at least in human omental adipose tissue explants, whereas Loeffelholz et al 17 observed a (non-significant) decrease of serum vaspin under conditions of euglycemic hyperinsulinemia.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…In the insulin-resistant group, vaspin significantly declined during the oGTT, somehow inversely mirroring the course of insulin. This finding is coherent with the observation of a meal-related decline in vaspin levels 11,16 and may indicate that glucose and/or insulin may have acute suppressive effects of circulating vaspin levels and/or that food-related effects such as vagal activation are involved. Tan et al 10 identified glucose as a vaspin-releasing agent, at least in human omental adipose tissue explants, whereas Loeffelholz et al 17 observed a (non-significant) decrease of serum vaspin under conditions of euglycemic hyperinsulinemia.…”
Section: Discussionsupporting
confidence: 76%
“…17,18 One explanation might be that some studies included subjects with an extreme phenotype in terms of insulin resistance and thus the metabolic effects could have overcome any potential impact of sex steroids on serum vaspin. Considering that children present a phase early in the pathological career of obesity-related comorbidities, but on the other hand are free of possibly interfering drugs, such as oral antidiabetic medications, 10,16 our data may support the conclusion of an adaptive response of vaspin to impaired glucose metabolism. 3 The association of vaspin with metabolic parameters was robustly significant in our cohort, independent from BMI SDS and hence the degree of obesity.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations